Effect of different protocols of caffeine intake on metabolism and endurance performance - Cox, G. R.; Desbrow, B.; Montgomery, P. G.; Anderson, M. E.; Bruce, C. R.; Macrides, T. A.; Martin, D. T.; Moquin, A.; Roberts, A.; Hawley, J. A.; Burke, L. M. (Journal of Applied Physiology, 2002)
Competitive athletes completed two studies of 2-h steady-state (SS) cycling at 70% peak O2 uptake followed by 7 kJ/kg time trial (TT) with carbohydrate (CHO) intake before (2 g/kg) and during (6% CHO drink) exercise. In Study A, 12 subjects received either 6 mg/kg caffeine 1 h preexercise (Precaf), 6 × 1 mg/kg caffeine every 20 min throughout SS (Durcaf), 2 × 5 ml/kg Coca-Cola between 100 and 120 min SS and during TT (Coke), or placebo. Improvements in TT were as follows: Precaf, 3.4% (0.2-6.5%, 95% confidence interval); Durcaf, 3.1% (0.1-6.5%); and Coke, 3.1% (0.2-6.2%). In Study B, eight subjects received 3 × 5 ml/kg of different cola drinks during the last 40 min of SS and TT: decaffeinated, 6% CHO (control); caffeinated, 6% CHO; decaffeinated, 11% CHO; and caffeinated, 11% CHO (Coke). Coke enhanced TT by 3.3% (0.8-5.9%), with all trials showing 2.2% TT enhancement (0.5-3.8%; P < 0.05) due to caffeine. Overall, 1) 6 mg/kg caffeine enhanced TT performance independent of timing of intake and 2) replacing sports drink with Coca-Cola during the latter stages of exercise was equally effective in enhancing endurance performance, primarily due to low intake of caffeine (~1.5 mg/kg).